Solid media based on Monochamus alternatus to growth and physiologically active substance of Paecilomyces tenuipes fruiting bodies - 하시영; 임우석; 김현철; 정지영; 양재경 (한국버섯학회지, 2024)
Paecilomyces tenuipes (P. tenuipes) is a fungus cultivated artificially by South Korean researchers, utilizing rice bran as its substrate. The increased demand for this fungus has not been met with successful cultivation methods for fruiting body production in natural environments. Therefore, we tested the effect on the growth of P. tenuipes using a Solid media based on pests. In this results, the Solid media based on M.alternatus was effective in increasing the growth of P. tenuipes and the content of cordycepin. Moreover, we confirmed the conditions for manufacturing a Solid media based on M.alternatus for P. tenuipes growth. We suggested that the growth-promoting compounds offers valuable insights for optimizing fungal cultivation conditions, thereby enhancing productivity and contributing to a broader understanding of fungal physiology in varying nutritional environments.